The Impact of Natural Resources and Foreign Aid On Governance: Evidence from The MENA Countries - Moharram, Dalia (AUC Knowledge Fountain, 2023)
Theoretical and empirical literature points out the “Curse of Natural Resources” where the abundance of resources in certain countries may hamper economic growth through several channels. The paper extends the previous research and investigates whether higher revenues- not only from natural resources’ rent but also from foreign aid- exhibit another type of curse in MENA countries. That is, do higher natural resources rent, and foreign aid erode the quality of institutions as measured by governance indicators in the MENA countries? This research utilizes a panel data fixed-effect model to investigate the abovementioned relationship during the period 2000-2020. The countries are divided into two groups: Gulf Cooperation Council (GCC) countries and the rest of the MENA countries. This research results indicate that natural resource abundance favorably impacts the quality of governance in the GCC countries but not the rest of the MENA countries. While foreign aid does impact the quality of governance in the GCC countries, it erodes this quality in the rest of MENA countries. These results exhibit some critical policy improvements for these countries in the future. Keywords: Natural resources abundance, Foreign aid, Governance, Gulf Cooperation Council (GCC), Middle East and North Africa (MENA) region.